Effect of the Substrate Biasing on the Structure and Properties of Tantalum Coatings Deposited Using HiPIMS in Deep Oscillations Magnetron Sputtering Mode - Fábio Ferreira; Albano Cavaleiro; João Oliveira (Metals, 2020)
The influence of energetic ion bombardment on the properties of tantalum coatings was studied. To achieve such energetic ion bombardment during the deposition process of tantalum coatings, a combination of deep oscillation magnetron sputtering (DOMS), an ionized physical vapour deposition technique, with substrate biasing was used. The substrate biasing was varied between 0 and −120 V. In this work, the structure (XRD), microstructure (SEM), surface morphology (AFM) and hardness, and Young’s modulus (nanoindentation) of the coatings were characterized. The results show with the use of such conditions it was possible to deposit a pure α-Ta (the most desired at industrial level) with improved mechanical properties (hardness equal to 22.4 GPa and Young’s modulus equal to 235 GPa). The roughness of the Ta coatings decreases up to values of about 1 nm with an increase of substrate biasing. It was possible to deposit very dense Ta coatings with 2 µm of thickness. Therefore, these results are significantly different than in previous works, offering Ta coatings with a combination of very interesting properties.